PELATIHAN DAN PENDAMPINGAN PEMBUATAN TEPUNG PISANG BARANGAN DI DESA SIGUCI KABUPATEN DELISERDANG, SUMATERA UTARA - Dewi Novina Sukapiring; Dini Novita Sari; Eka Nenni Jairani; Jane Melita Keliat (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Siguci Village is one of the barangan banana producing villages in North Sumatera. The processing of banana has great prospect as one of business opportunities that increase the income of the local community. One of the processed products that can be made from barangan banana is banana flour the purpose of this training is to increase the understanding of the people of Siguci Villagr about the alternative processing of banana goods into banana flour. The method of implementation is by conducting training and direct assistance in the manufature of banana flour and conducting pre-test dan post-test based on the results of pre-test with an averange value of 23,3 and post-test with an averange value of 65 so it can be concluded that there is an increase in public understanding of the alternative processing of banana goods